2019
DOI: 10.1080/09168451.2019.1608802
|View full text |Cite
|
Sign up to set email alerts
|

Peppermint (Mentha piperita L.) extract effectively inhibits cytochrome P450 3A4 (CYP3A4) mRNA induction in rifampicin-treated HepG2 cells

Abstract: Interaction between foods and drugs is an important consideration in pharmaceutical therapy. Therefore, here, we examined the suppressive effects of the extracts from seven edible herbs on the induction of CYP3A4 gene expression in rifampicin-treated HepG2 cells. We evaluated the structure and suppressive activity of the most effective active compound isolated from dried peppermint (Mentha piperita L.). The structure of the compound was identified as that of pheophorbide a based on spectroscopic data. It suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The results showed that epimedium inhibited CYP3A4 transcription without any cytotoxicity. Dexamethasone alone at a low concentration of 10 μM induced CYP3A4 mRNA, similar to rifampin (a CYP3A4 enhancer ( Kobayashi et al, 2019 )). However, in combination with epimedium, we observed 50% less suppression of CYP3A4 mRNA expression.…”
Section: Discussionmentioning
confidence: 96%
“…The results showed that epimedium inhibited CYP3A4 transcription without any cytotoxicity. Dexamethasone alone at a low concentration of 10 μM induced CYP3A4 mRNA, similar to rifampin (a CYP3A4 enhancer ( Kobayashi et al, 2019 )). However, in combination with epimedium, we observed 50% less suppression of CYP3A4 mRNA expression.…”
Section: Discussionmentioning
confidence: 96%
“…Peppermint tea inhibits CYP3A4 induction by rifampicin in vitro [95]; oil: contradicting results on CYP inhibition in vitro [96,97]; enhanced cyclosporine bioavailability in rats [98] Cyclosporine, tacrolimus?…”
Section: Peppermintmentioning
confidence: 99%